Divided by borders : Mexican migrants and their children - Dreby, Joanna, 1976- (University of California Press, 2010)
Since 2000, approximately 440,000 Mexicans have migrated to the United States every year. Tens of thousands have left children behind in Mexico to do so. For these parents, migration is a sacrifice. What do parents expect to accomplish by dividing their families across borders? How do families manage when they are living apart? More importantly, do parents' relocations yield the intended results? Probing the experiences of migrant parents, children in Mexico, and their caregivers, Joanna Dreby offers an up-close and personal account of the lives of families divided by borders. What she finds i.